2013
DOI: 10.1158/1538-7445.am2013-3290
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3290: Modulation of AKT, ERK and Mcl-1 by apigenin sensitizes colon cancer cells to anti-tumor activities of ABT263.

Abstract: Apigenin is an edible plant-derived flavonoid showing anti-tumor activities in vitro and in vivo. Pretreatment with apigenin resulted in cell growth arrest and/or apoptosis in various types of tumors via modulating multiple cell signaling pathways. In the present study, we evaluated interactions between apigenin and ABT263 in multiple colon cancer cell lines. We found that apigenin enhanced ABT263-induced apoptosis in colon cancer cells in a time- and dose-dependent manner. ABT263 alone only res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, Ding et al demonstrated that quercetin reduced cell viability, induced apoptosis, cleaved caspase-3, cleaved PARP, upregulated Bax protein expression, and downregulated p-ERK1/2 protein levels in HepG2 cells [ 57 ]. Shao et al demonstrated that phytochemicals, such as apigenin (one of the flavonoids present in MH), downregulates the activation of ERK and Akt in human colon cancer cells [ 58 ]. Moreover, ERK1/2 has been previously implicated with β-catenin, mTOR, and cyclin D1 in cellular proliferation [ 39 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ding et al demonstrated that quercetin reduced cell viability, induced apoptosis, cleaved caspase-3, cleaved PARP, upregulated Bax protein expression, and downregulated p-ERK1/2 protein levels in HepG2 cells [ 57 ]. Shao et al demonstrated that phytochemicals, such as apigenin (one of the flavonoids present in MH), downregulates the activation of ERK and Akt in human colon cancer cells [ 58 ]. Moreover, ERK1/2 has been previously implicated with β-catenin, mTOR, and cyclin D1 in cellular proliferation [ 39 , 59 ].…”
Section: Discussionmentioning
confidence: 99%